Hemophilia gene therapy knowledge and perceptions: Results of an international survey. Issue 4 (19th March 2020) - Peyvandi, Flora; Lillicrap, David; Mahlangu, Johnny; McLintock, Claire; Pasi, K. John; Pipe, Steven W.; Scales, Wendy; Srivastava, Alok; VandenDriessche, Thierry
Abstract: Background: Hemophilia gene therapy is a rapidly evolving therapeutic approach in which a number of programs are approaching clinical development completion. Objective: The aim of this study was to evaluate knowledge and perceptions of a variety of health care practitioners and scientists about gene therapy for hemophilia. Methods: This survey study was conducted February 1 to 18, 2019. Survey participants were members of the ISTH, European Hemophilia Consortium, European Hematology Association, or European Association for Hemophilia and Allied Disorders with valid email contacts. The online survey consisted of 36 questions covering demographic information, perceptions and knowledge of gene therapy for hemophilia, and educational preferences. Survey results were summarized using descriptive statistics. Results: Of the 5117 survey recipients, 201 responded from 55 countries (4% response rate). Most respondents (66%) were physicians, and 59% were physicians directly involved in the care of people with hemophilia. Among physician respondents directly involved in hemophilia care, 35% lacked the ability to explain the science of adeno‐associated viral gene therapy for hemophilia, and 40% indicated limited ability or lack of comfort answering patient questions about gene therapy for hemophilia based on clinical trial results to date. Overall, 75% of survey respondents answered 10 single‐answer knowledge questions correctly, 13% incorrectly, and 12% were unsure of the correct answers. Conclusions: This survey highlighted knowledge gaps and educational needs related to gene therapy for hemophilia and, along with other inputs, has informed the development of "Gene Therapy in Hemophilia: An ISTH Education Initiative."